The Epidemiology of Meningococcal Disease and Carriage, Genotypic Characteristics and Antibiotic Resistance of Neisseria meningitidis Isolates in Zhejiang Province, China, 2011–2021 - Zhang, Yunyi; Deng, Xuan; Jiang, Yan; Zhang, Junyan; Zhan, Li; Mei, Lingling; Lu, Hangjing; Yao, Pingping; He, Hanqing (Frontiers in Microbiology, 2022)
Neisseria meningitidis (Nm) remains a worldwide leading cause of epidemic meningitis. During 2011-July 2021, fifty-five meningococcal disease (MD) cases were reported with the case fatality rate of 5.45% in Zhejiang Province, China. The median age was 7 years old. The annual incidence was 0.0017-0.0183 per 100,000 population. The highest age-specific incidence was observed in the group of <1 year old. Serogroup was identified in 30 laboratory-confirmed MD cases, and MenB was most predominant. MenB was mainly observed in two age groups: < 5 years old and > 35 years old. MenB incidence was significantly increasing from 0.0018 per 100,000 in 2013 to 0.0070 per 100,000 in 2019. During 2015-2020, seventeen positive samples were detected from 2827 throat swabs from healthy population, of which 70.59% was MenB. Twenty Multi-locus sequence typing (MLST) sequence types (STs) containing eight newly assigned STs (ST15881 - ST15888) were determined in all Nm isolates. Either in MD cases or in healthy population, MenB CC ST-4821 was the predominant sequence type. It was worth noting that two Men Y CC ST-23 cases occurred in 2019 and 2021, respectively. MenY CC ST-23 MD cases increased gradually in China. Phylogeny results based on genome sequencing indicated that Chinese Men W CC ST-11 isolates were genetically linked, and grouped together with Japanese isolates, separated from Men W CC ST-11 isolates from Saudi Arabia Hajj outbreak, Europe, South Africa, South America, North America and Oceania. Men W CC ST-11 isolates from East Asia might have evolved locally. Antibiotic susceptibility tests revealed a relatively high resistance rate (22.86%) of Nm isolates to penicillin. This study provided valuable data for Chinese public health authorities to grasp the temporal epidemiological characteristics of MD and healthy carriage.